PENINGKATAN KEMAMPUAN BELAJAR PPKN MELALUI METODE GAME-BASED LEARNING DENGAN MEDIA WORDWALL PADA SISWA KELAS X E DI SMA NEGERI 6 MADIUN - Neila Nur Ni’ma; Nurhadji Nurhadji; Mahfud Fauzi (Kampus Akademik Publiser, 2024)
This study aims to enhance the quality of critical thinking education for grade X E students at SMAN 6 Madiun through the implementation of the Games-Based Learning model. Facing the challenges of 21st-century education, it is crucial for all parties, including the government, the community, and teachers, to collaborate in improving the quality of education. This classroom action research (CAR) involves two cycles with stages of planning, action, observation, and reflection. The research methods include direct observation, interviews with students and teachers, and evaluation of student learning outcomes. Data analysis was conducted both qualitatively and quantitatively. In the first cycle, only 20 out of 37 students met the established critical understanding indicators (CUIs). After reflection and improvements in the second cycle, the number of students meeting the CUIs increased to 31, showing a 29% improvement. The results indicate that the Games-Based Learning model is effective in enhancing students' critical thinking skills. Implementing this model makes learning more engaging and interactive, encouraging student involvement and improving their critical thinking abilities. Based on these findings, the Games-Based Learning approach is recommended for application in other subjects, with adjustments made according to students' needs. This study concludes that with proper planning and appropriate learning strategies, the quality of education can be significantly improved..